Linguistic Corpus of the Caro y Cuervo Institute (CLICC): an online platform for corpus storage, systematization and consultation - Rubio López, Ruth (2023)
Corpus Lingüísticos del Instituto Caro y Cuervo (CLICC) is an online platform for corpus storage, systematization, administration, and query. CLICC was created with the objective of safeguarding the files produced by research conducted by the Institute. Now, it is available so that researchers, communities, or interested people can publish their corpora of Colombian languages. CLICC is a free access space open to the general and specialized public interested in exploring and contributing to the documentation of Colombia's linguistic and cultural diversity. This document describes its characteristics, functionalities, consultations, and future perspectives. It also highlights the various changes that have been made to guarantee the publication of different types of corpora, the permissions and singularity of each corpus, and the future use of the documents for various purposes.